Design aspects of a high speed monohull RoPax ferry - Kluwe, Florian; Martinsen, Kay; Krüger, Stefan; Lübcke, Adele; Will, Johannes (ASME, 2015)
This paper describes the design process of a high speed mono hull RoPax ferry which operates at a Froude number of 0.4. The design task was quite challenging, as two possible transport concepts were in principle possible: Two ships were needed with a total speed of 50knots, which could result in a combination of a 30kn high speed Catamaran plus a conventional 20kn RoPax Ferry or alternatively in two identical sister vessels of 25kn each. The solution with the high speed catamaran plus the conventional RoPax-Ferry defined the total cost budget, which must not be exceeded by the design of the two sister vessels. This resulted in a tough boundary condition and made life cycle cost evaluations necessary. Due to harbor restrictions, the length of the ships was limited by abt. 110m, resulting in a Froude number of abt. 0.4. This resulted in high costs for the propulsion system. The ferries should initially have open RoRo-Cargo spaces for cost reasons, which made the stability requirements (weather criterion plus Stockholm Agreement) quite challenging. This also strongly influenced the design of the final hull form. As the ship is very sensitive to weight, detailed steel structure optimizations had to be carried out to optimize the main grillage systems of the vehicle decks. The hull form and the appendage design required careful optimization to guarantee the required service speed with the engine power which was available in the price budget. As no vessel of comparison was available, the speed power estimation as well as all design tasks had fully to rely on numerical predictions. As the ship had further demanding requirements for course keeping and comfort in waves, the optimization of the hull form must include also these issues. The paper shows that the design of complex ships is actually a holistic task which includes many engineering disciplines. The paper also shows that 1st principle based design methods can support the design process of specialized vessels significantly.